OBSERVATIONS ON THE INDIAN MACKEREL, RASTRELLIGER CANAGURTA (CUV) FROM PURSE-SEINE CATCHES ALONG GOA COAST - Doiphode, P V (Indian Journal of Fisheries, 2011)
The present study is based on 351 specimens of the Indian mackerel (Rastrelliger kanagurta) collected during the period October, 1965 to January, 1966 from the purse-seine catches at Panaji. No appreciable difference between males and females has been noticed in the length-weight relationship of mackerel observed in present investigation. The predominant group in the food item was Dinophyceae constituting about 50.3% in count value. The other important groups were Diatoms, Copepods, Bivalves and Miscellaneous items.